Enhancement of thermoelectric performance in n-type PbTe1−ySey by doping Cr and tuning Te:Se ratio. (April 2015) - Chere, Eyob K.; Zhang, Qian; McEnaney, Kenneth; Yao, Mengliang; Cao, Feng; Sun, Jingying; Chen, Shuo; Opeil, Cyril; Chen, Gang; Ren, Zhifeng
Abstract: Lead telluride and its alloys have been extensively studied for medium temperature thermoelectric applications due to decent figure-of-merit ( ZT ) at temperature close to 900 K. However, little emphasis has been given to improve the ZT near room temperature. In this investigation, we report a systematic study of Cr doping in PbTe1− y Se y with y =0, 0.25, 0.5, 0.75, 0.85, and 1. We found the peak ZT temperature increased with increasing concentration of Se. The highest ZT of ~0.6 at room temperature in Te-rich Cr0.015 Pb0.985 Te0.75 Se0.25 was obtained due to a lowered thermal conductivity and enhanced power factor resulted from high Seebeck coefficient of about −220 µV K −1 and high Hall mobility ~1120 cm 2  V −1  s −1 at room temperature. A room temperature ZT of ~0.5 and peak ZT of ~1 at about 573–673 K is shown by Se-rich sample Cr0.01 Pb0.99 Te0.25 Se0.75 . This improvement of the room temperature ZT improved the average ZT over a wide temperature range and could potentially lead to a single leg efficiency of thermoelectric conversion for Te-rich Cr0.015 Pb0.985 Te0.75 Se0.25 up to ~11% and Se-rich Cr0.01 Pb0.99 Te0.25 Se0.75 up to ~13% with cold side and hot side temperature at 300 K and 873 K, respectively, if matched with appropriate p-type legs. Graphical abstract: Highlights: We achieved the highest room temperature ZT of ~0.6 by optimizing Cr doping. The peak ZT temperature increased with increasing concentration of Se. The average ZT improved due to improvement of room temperature ZT . Thermoelectric conversion efficiency of up to 13% could be achieved.